Digital banking in Singapore - Lim, Kevin (2022)
Due to the changing landscape technology has taken over many industries by storm, especially so within the financial hub of banking in Singapore where many new competitions are sprouting out to compete with banks directly and indirectly. There is a requirement for banks to improve their processes and enhance their user experience through digitization (I.E. Transforming to Digital Banks) in order to stay relevant.